A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India - Balasubramanian, Chellaiah; Muthukatturaja, Marimuthu (Zootaxa, 2019)
A new mayfly species Thraulus thiagarajani sp. nov. is described and characterized by dorsal lamella of abdominal gill I lanceolate, lamella of gills II- VII subequal to or slightly larger than dorsal lamella; posterior margin of labrum not strongly convex. Imago of the species with patterned femora and tergum. Hind wings have no coloration at base, much smaller than forewing. Costal projection is present at 0.6 of hind wing.